Human myiasis caused by the reindeer warble fly, Hypoderma tarandi, case series from Norway, 2011 to 2016 - Landehag, Jörgen; Skogen, Andreas; Åsbakk, Kjetil; Kan, Boris (European Centre for Disease Prevention and Control, 2017)
Source at http://dx.doi.org/10.2807/1560-7917.ES.2017.22.29.30576 Hypoderma tarandi causes myiasis in reindeer and caribou ( Rangifer tarandus spp.) in most northern hemisphere regions where these animals live. We report a series of 39 human myiasis cases caused by H. tarandi in Norway from 2011 to 2016. Thirty-two were residents of Finnmark, the northernmost county of Norway, one a visitor to Finnmark, and six lived in other counties of Norway where reindeer live. Clinical manifestations involved migratory dermal swellings of the face and head, enlargement of regional lymph nodes, and periorbital oedema, with or without eosinophilia. Most cases of human myiasis are seen in tropical and subtropical countries, and in tourists returning from such areas. Our findings demonstrate that myiasis caused by H. tarandi is more common than previously thought. Healthcare professionals in regions where there is a likelihood of human infestation with H. tarandi (regions populated by reindeer), or treating returning travellers, should be aware of the condition. All clinicians are advised to obtain a detailed travel history when assessing patients with migratory dermal swellings. On clinical suspicion, ivermectin should be given to prevent larval invasion of the eye (ophthalmomyiasis). Since H. tarandi oviposits on hair, we suggest wearing a hat as a prevention measure.